Stop the Clock Policies and Career Success in Academia - Manchester, Colleen Flaherty; Leslie, Lisa M; Kramer, Amit (American Economic Review, 2010)
Stop the Clock Policies and Career Success in Academia by Colleen Flaherty Manchester, Lisa M. Leslie and Amit Kramer. Published in volume 100, issue 2, pages 219-23 of American Economic Review, May 2010